2018
DOI: 10.1002/jssc.201800086
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of five high‐purity iridoid glycosides from Gardenia jasminoides Eills by molecularly imprinted solid‐phase extraction integrated with preparative liquid chromatography

Abstract: Five iridoid glycosides were prepared using molecularly imprinted solid-phase extraction combined with preparative high-performance liquid chromatography. Hydrophilic molecularly imprinted polymers were synthesized using α-1-allyl-2-N-acetyl glucosamine, which introduced an abundance of hydrophilic groups into the polymers. Using molecularly imprinted solid-phase extraction as the sample pretreatment procedure, five iridoid glycosides, gardenoside, geniposide, shanzhiside, geniposidic acid, and genipin-1-O-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Geniposidic acid is one of the representative active ingredients in Fructus Gardeniae [15,16], which was chosen as one of the quality control markers of this herb [17,18]. In recent years, researchers have demonstrated that geniposidic acid has better plasma absorption and tissue distribution in pathological states [19].…”
Section: Introductionmentioning
confidence: 99%
“…Geniposidic acid is one of the representative active ingredients in Fructus Gardeniae [15,16], which was chosen as one of the quality control markers of this herb [17,18]. In recent years, researchers have demonstrated that geniposidic acid has better plasma absorption and tissue distribution in pathological states [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, finding six potential lactate dehydrogenase inhibitors from Belamcanda chinensis [13], and screening compounds from the leaves of Ligustrum lucidum Ait as potent neuraminidase inhibitors [14]. A molecularly imprinted SPE was used to concentrate a kind of compounds and it integrated with prep-HPLC for preparation of active iridoid glycosides from Gardenia jasminoides Eills [15].…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are prepared by using MIT with tailor‐made recognition sites for a given analyte and its structural analogs . MIPs present high specificity, desired selectivity, thermal stability, as well as low costs and easy preparation, which make them ideal materials for separation science . In the preparation process, MIPs are always obtained by bulk polymerization, precipitation polymerization, and suspension polymerization .…”
Section: Introductionmentioning
confidence: 99%